2017
DOI: 10.1007/s00426-017-0892-4
|View full text |Cite
|
Sign up to set email alerts
|

Intentional binding of two effects

Abstract: An action that produced an effect is perceived later in time compared to an action that did not produce an effect. Likewise, the effect of an action is perceived earlier in time compared to a stimulus that was not produced by an action. Despite numerous studies on this phenomenon-referred to as Intentional Binding effect (IB)-the underlying mechanisms are still not fully understood. Typically, IB is investigated in settings where the action produces just one single effect, whereas in everyday action contexts, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
21
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(25 citation statements)
references
References 32 publications
3
21
1
Order By: Relevance
“…Nonetheless, the 250 ms action-outcome interval used by Haggard et al [2] is the most standard delay used in the temporal binding literature, and is sometimes used as the single delayed interval, or intermixed with other delays (e.g., [20]- [22]). Moreover, an interval of 250 ms between action and outcome appears to cause a larger temporal binding effect than other intervals [2], [23].…”
Section: Methodsmentioning
confidence: 88%
“…Nonetheless, the 250 ms action-outcome interval used by Haggard et al [2] is the most standard delay used in the temporal binding literature, and is sometimes used as the single delayed interval, or intermixed with other delays (e.g., [20]- [22]). Moreover, an interval of 250 ms between action and outcome appears to cause a larger temporal binding effect than other intervals [2], [23].…”
Section: Methodsmentioning
confidence: 88%
“…While perceived causality has been investigated in several different ways (e.g., causal model selection, Lagnado and Sloman, 2004; numbers of causal links selected, Lagnado and Sloman, 2006; judgment of time passed, Ruess et al 2018), this research has mostly focused on the perceived impact of one event (e.g., a button pressed by a study participant) on a second event (e.g., a red light turning on). We, on the other hand, study the perceived impact of a single action on an overall outcome, which implies a value judgment regarding which actions are important in general and affects even the choice between different courses of actions.…”
Section: Late-action Bias: Perceived Outcome Reversibility and Heightmentioning
confidence: 99%
“…In general, people are more likely to say that event A is the cause of event B when event B follows event A closely in time rather than when it is delayed. Interesting enough, the reverse also happens, such that people are more likely to perceive the time between an event and an outcome as shorter when the relationship is considered to be causal, in a process called "intentional binding" (Buehner, 2012;Faro, McGill, & Hastie, 2013;Ruess, Thomaschke, Haering, Wenke, & Kiesel, 2018;Ruess, Thomaschke, & Kiesel, 2017). For instance, people report shorter time intervals between causally related historical events compared to causally unrelated events, suggesting that causality is simply viewed as key in assessing temporal distance (Faro, McGill, & Hastie, 2010).…”
Section: Time In Causality Judgmentsmentioning
confidence: 99%
“…This is not surprising given that our everyday physical movements can generate multiple outcomes and they can be executed in response to a sensory event, such as "go" trigger. Indeed, recent studies have demonstrated that intentional binding can emerge for two consecutive outcomes initiated by a single keypress, that is, the perceived timing of both events are attracted towards the action (Ruess, Thomaschke, Haering, Wenke, & Kiesel, 2018), suggesting that intentional binding cannot be limited to a single action-outcome dyad.…”
Section: Is Intentional Binding Limited To Action-outcome Dyad?mentioning
confidence: 99%